Synthesis and electrochemical characterization of amorphous manganese-nickel oxide as supercapacitor electrode material - Chan, Pei Yi; Majid, Siti Rohana (Springer Verlag (Germany), 2018)
An amorphous composite film consisted of manganese and nickel oxide was synthesized using simple chronopotentiometry method and tested as electrode material for supercapacitor. The composite film was examined using X-ray diffraction, transmission electron microscopy, and electrochemical characterizations. The electrochemical characterization was performed using cyclic voltammetry, galvanostatic charge-discharge, and frequency response analyzer by a three-electrode configuration. The prepared composite electrode remained amorphous until 400 °C. The composite film deposited at 13 min and annealed at 300 °C was found to perform the best. It exhibited a good specific capacitance of 670 F g−1 over a potential window of 1 V in 1 M Na2SO4. Annealing temperature higher than 300 °C brought about a rapid decrease in specific capacitance. The composite electrode remained 61% of initial specific capacitance after 1000 cycles.